Antimicrobial resistance in zoonotic bacteria in Bangladesh: a converging crisis at the human–animal–environment interface - Kabir, S M Lutful (Asian Journal of Medical and Biological Research, 2026)
Abstract not available Asian J. Med. Biol. Res. 2026, 12(1), 1-4